Pengaruh Penggunaan Gadget terhadap Perkembangan Anak Usia Dini Prasekolah di TK Kemala Bhayangkari 3 Padang - Alsri Windra Doni; Dewi Susanti; Aprizal Ponda (Jurnal Sehat Mandiri, 2019)
Preschool children experience a rapid process of physical, motoric, intellectual, emotional, language and social development. One thing that influences development is gadgets. Gadgets are equipped with features such as social media, video, audio, images and games so that children become addicted and become lazy about moving or doing activities. The aim of this research is to determine the effect of gadget use on the development of preschool children at Kemala Bhayangkari 3 Padang Kindergarten. The research uses an Analytical Survey design with a cross sectional approach. Data collection was carried out at Kindergarten Kemala Bhayangkari 3 Padang from 10-24 May 2017 with a sample size of 55 people. The sampling technique is saturated sampling with a questionnaire and KPSP format. Data processing uses the chi-square statistical test. The research results showed that 67.3% of respondents were not normal in using gadgets, 50.9% of respondents had deviant development. The results of the bivariate analysis obtained p-value=0.007, meaning that there is a significant relationship between gadget use and the development of preschool-aged children. The conclusion is that there is a significant relationship between gadget use and the development of preschool children. It is hoped that the school will continue to pay attention to children's development and provide stimulus to achieve appropriate development. For parents to limit their children's use of gadgets to 30 minutes a week.